2014
DOI: 10.1177/2153368714554717
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Police Reporting Among Hispanic Immigrant Victims of Violence

Abstract: The purpose of this study was to examine predictors of police reporting among Hispanic immigrant victims of violence. A sample of 127 Hispanic immigrants was generated through a chain-referral procedure in the city of Hempstead, New York. Participants were asked about their most recent victimization experiences, and detailed information was collected on up to three incidents. The analyses were based on a total of 214 separate victimization incidents, one third of which were reported to the police. Logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Less empirical research has paid attention to the impact of victim-offender relationships on reporting crimes, with most studies concentrating on sexual offense crimes (Baumer et al, 2003;Guadriaan, 2006;Felson et al, 2002). Others have drawn attention to assault crimes (Sidebottom, 2015) and racial factors (Hautala et al, 2015). Therefore, by revealing the extent to which victim-offender relationships influence reporting property crimes to the police, this study contributes to the body of knowledge on reporting crimes.…”
Section: A Influence Of Victim-offender Relationship On Reporting Pro...mentioning
confidence: 86%
See 1 more Smart Citation
“…Less empirical research has paid attention to the impact of victim-offender relationships on reporting crimes, with most studies concentrating on sexual offense crimes (Baumer et al, 2003;Guadriaan, 2006;Felson et al, 2002). Others have drawn attention to assault crimes (Sidebottom, 2015) and racial factors (Hautala et al, 2015). Therefore, by revealing the extent to which victim-offender relationships influence reporting property crimes to the police, this study contributes to the body of knowledge on reporting crimes.…”
Section: A Influence Of Victim-offender Relationship On Reporting Pro...mentioning
confidence: 86%
“…The victim-offender relationship is a primary factor in this research that impacts one's readiness to report property crime to the police. A large number of studies have found that the victim-offender relationship is an important factor influencing crime reporting behavior (Bunei et al, 2012;Felson et al, 2002;Hautala et al, 2015). However, most studies on the effect of the victim-offender relationship on @ @ @ @ crime reporting have focused on sexual offenses, leaving a gap in the literature on property crime reporting studies, which this study intends to fill.…”
Section: Introductionmentioning
confidence: 95%